Amoebic Liver Abscess and Indigenous Alcoholic Beverages in the Tropics. (10th July 2018) - Kumanan, T.; Sujanitha, V.; Balakumar, S.; Sreeharan, N.
Abstract : Amoebic liver abscess (ALA) seen commonly in the tropics is predominantly confined to adult males, especially those who consume locally brewed alcohol, although intestinal amoebiasis occurs in all age groups and in both genders. Whether the role of alcohol in the development of ALA is incidental and casual or whether alcohol is causally implicated has been debated. It has been argued that socioeconomic factors and poor sanitary conditions are the primary culprits that casually link alcohol to ALA. However, there has emerged an abundance of data that implicates alcohol in a more causal role in facilitating the extraintestinal invasion of the infective protozoan and the subsequent development of ALA. These factors include the role of alcohol in host immunity, parasitic proliferation, and invasion and in creating a conducive hepatic microenvironment. The contributory role of alcohol-induced increase in hepatic iron stores and lipid content is discussed. Late-stage liver disease with fibrosis seems to be protective for the development of ALA. Further research is necessary to elucidate the many possible mechanisms that predispose to hepatic amoebiasis, so that appropriate individual and population-based preventive measures can be implemented.